2014
DOI: 10.1111/ajt.12531
|View full text |Cite
|
Sign up to set email alerts
|

Postanastomotic Transplant Renal Artery Stenosis: Association With De Novo Class II Donor-Specific Antibodies

Abstract: In this study, we analyze the outcomes of transplant renal artery stenosis (TRAS), determine the different anatomical positions of TRAS, and establish cardiovascular and immunological risk factors associated with its development. One hundred thirty-seven of 999 (13.7%) patients had TRAS diagnosed by angiography; 119/137 (86.9%) were treated with angioplasty, of which 113/137 (82.5%) were stented. Allograft survival in the TRASþ intervention, TRASþ nonintervention and TRASÀ groups was 80.4%, 71.3% and 83.1%, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 35 publications
1
52
0
2
Order By: Relevance
“…Transplant renal artery stenosis (TRAS) is associated with allograft dysfunction, refractory hypertension and inferior allograft survival in the absence of prompt intervention (1)(2)(3). There is significant variability in the reported incidence of TRAS (1-25%) likely secondary to institutional variation of screening protocols, thresholds for intervention and baseline patient demographics (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transplant renal artery stenosis (TRAS) is associated with allograft dysfunction, refractory hypertension and inferior allograft survival in the absence of prompt intervention (1)(2)(3). There is significant variability in the reported incidence of TRAS (1-25%) likely secondary to institutional variation of screening protocols, thresholds for intervention and baseline patient demographics (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…There is significant variability in the reported incidence of TRAS (1-25%) likely secondary to institutional variation of screening protocols, thresholds for intervention and baseline patient demographics (1)(2)(3)(4)(5)(6)(7)(8). The management of TRAS is more widely agreed upon with endovascular intervention (EVI) playing a significant role in preserving graft function and prolonging graft survival (1,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have reported that transplant renal artery stenosis occurs more frequently in patients with episodes of acute rejection and in the presence of donor specific antibodies (14,15), and episodes of acute rejection have been decreasing over time due to improvements in immunosuppressive therapies over time (16).…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication focusing on transplant renal artery stenosis in single grafts from adult donors suggested that stenosis is a heterogeneous disease process with associations between the location of stenosis (anastomotic vs. postanastomotic) and alloimmunity, recipient cardiovascular risk factors, and living versus deceased donors (15). In the study by Willicombe et al, anastomotic transplant artery stenosis was more likely to develop in living donor recipients, whereas postanastomotic stenosis was associated with older deceased donors (15). Given the absence of stenoses clearly separate from the anastomosis and of more distal stenoses (including of the proper renal arteries) in our cohort, our data suggest that such cases are extremely rare or perhaps nonexistent in EBKT recipients.…”
Section: Discussionmentioning
confidence: 99%